MODAL INTELEKTUAL DALAM PENGEMBANGAN EKONOMI KREATIF: STUDI KASUS PADA SENTRA KERAJINAN SEPATU CIBADUYUT BANDUNG - Yuhana Astuti; Annisa Anggraini (Jurnal Manajemen Indonesia, 2015)
The concept of Creative Economy is a concept in a new economic era which intensifies on information and creativity, by relying on the ideas and the stock of knowledge of Human Resources, as a major production factor in their economic activities. This case study aims not only to determine how is the image of the intellectual capital (IC) in Cibaduyut shoe craft centers in Bandung-Indonesia but also to find the appropriate alternative strategy that can be applied by SMEs in shoe Cibaduyut shoe craft centers in order to compete in the ASEAN Economic Community by 2015. The data collection technique is using triangulation and self assessment by using ICS (Intellectual Capital Statement) as an instrument that used to define the factors of IC, then evaluate it with QQS (Quality, Quantity, Systemetic) assessment and analysis with management IC portfolio. The results showed: (1). There are three additional of IC components in SMEs of Cibaduyut Shoes Centers Bandung, such as the skills, technology, and patents, (2). IC Human Capital is a weakness of SMEs Cibaduyut shoe craft centers while IC Relational Capital is the strength. As for to gain sustainable development of creative economy, it need to focus on the development of human capital